Global Pesticide Resistance in Arthropods 2008
DOI: 10.1079/9781845933531.0032
|View full text |Cite
|
Sign up to set email alerts
|

Documentation of pesticide resistance in arthropods.

Abstract: This chapter provides a more detailed presentation of the 7747 cases of arthropod resistance. Cases are organized by species and include information on resistant compounds and geographic sites of resistance. Information from this chapter can be found online in the APRD (http://www.pesticideresistance.com).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
81
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(81 citation statements)
references
References 0 publications
0
81
0
Order By: Relevance
“…Another study demonstrated that cytochrome p450 inhibition in L . decemlineata using piperonyl butoxide re-establishes a more susceptible population [ 8 ]. When we examined up-regulated genes in two resistant populations, we found many possible mechanisms of resistance that could play a role in detoxification of imidacloprid including multiple up-regulated cytochrome p450s.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study demonstrated that cytochrome p450 inhibition in L . decemlineata using piperonyl butoxide re-establishes a more susceptible population [ 8 ]. When we examined up-regulated genes in two resistant populations, we found many possible mechanisms of resistance that could play a role in detoxification of imidacloprid including multiple up-regulated cytochrome p450s.…”
Section: Discussionmentioning
confidence: 99%
“…decemlineata are developing resistance to neonicotinoid insecticides, including field populations in Wisconsin, Maine, Michigan and New York [ 2 , 4 7 ]. Resistant populations of beetles are typically classified using LC 50 assays, where the estimated ratio (RR) is calculated as the ratio of the estimated LC 50 of the test population over the LC 50 of a reference susceptible population [ 8 ]. If the RR value is greater than 10, a population is considered to have (or to be trending towards) a resistant phenotype.…”
Section: Introductionmentioning
confidence: 99%
“…With global warming, increased international travel, and tainted fresh water pools, a number of mosquitoes are distinctly increasing in incidence with a high occurrence of dengue fever all over the globe [ 9 , 10 ]. Widespread insecticide resistance [ 11 ] has been a major obstacle in the cost-effective integrated mosquito management program. In addition, the number of approved insecticides may be reduced in the near future in the US [ 12 ] and in the European Union [ 13 ] because of re-registration of conventional insecticides.…”
Section: Introductionmentioning
confidence: 99%
“…Resistance of insects to pesticide sprays in agriculture has been observed for a century (Melander, 1914). Under selection pressure by pesticide applications, thousands of cases of pesticide resistance in hundreds of arthropod species have been recorded (Mota-Sánchez et al, 2008). Since the fi rst report of insect resistance to Bacillus thuringiensis (Bt) in 1985(McGaughey, 1985, the potential for the development of insect resistance to Bt has been well demonstrated by the laboratory selection of various insects with resistance to Bt toxins (Tabashnik, 1994;Ferré and Van Rie, 2002;Bravo and Soberón, 2008).…”
Section: Introductionmentioning
confidence: 99%